Food Grade Pimenta Leaf Essential Oil Reduces the Attachment of Salmonella enterica Heidelberg (2011 Ground Turkey Outbreak Isolate) on to Turkey Skin - Nair, Divek V. T.; Kollanoor Johny, Anup (Frontiers in Microbiology, 2017)
Salmonella attached to the poultry skin is a major source of carcass contamination during processing. Once attached to the poultry skin, it is difficult to detach and inactivate Salmonella by commonly used antimicrobial agents since the pathogen is entrapped deeply in the feather follicles and the crevices on the skin. Essential oils could be natural, safe, and effective alternatives to synthetic antimicrobial agents during commercial and organic processing setup. The present study evaluated the efficacy of pimenta (Pimenta officinalis Lindl.) leaf essential oil (PEO), and its nanoemulsion in reducing Salmonella Heidelberg attachment on to turkey (Meleagris gallopavo) skin during simulated scalding (65oC) and chilling (4oC) steps in poultry processing. A multidrug resistant S. Heidelberg isolate from the 2011 ground turkey outbreak in the USA was used in the study. Results showed that PEO and the nanoemulsion resulted in significant reduction of S. Heidelberg attachment on turkey skin. Turkey skin samples treated with 1.0% PEO for 5 min resulted in >2 log10 CFU/sq. inch reduction of S. Heidelberg at 65 and 4oC, respectively (n=6; P<0.05). Similarly, skin samples treated with 1.0% pimenta nanoemulsion (PNE) for 5 min resulted in 1.5- and 1.8- log10 CFU/sq. inch reduction of S. Heidelberg at 65 and 4oC, respectively (n=6; P<0.05). In addition, PEO and PNE were effective in reducing S. Heidelberg on skin during short-term storage at 4 and 10oC (temperature abuse) (n=6; P<0.05). No Salmonella was detected in the dipping solution containing 0.5 or 1.0% PEO or PNE, whereas a substantial population of the pathogen survived in the control dipping solution. The results were validated using scanning electron -, and confocal - microscopy techniques. PEO or PNE could be utilized as an effective antimicrobial agent to reduce S. Heidelberg attachment to turkey skin during poultry processing.